Novel Treatment Strategies for Glioblastoma - Stylli, Stanley (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This book is a compilation of articles that brings together current knowledge from an international team of contributors who are dedicated investigators exploring novel strategies for the treatment of glioblastoma. These articles describe some of the latest concepts that will provide students, researchers and clinicians with an overview of the therapeutic approaches being developed in the field of neuro-oncology to combat this deadly disease.